Principal’s Personality Competence in Islamic Education from the Perspective of Interpretation of the Qur’an - Siti Qomariyah; Yurna Yurna; Irma Muti; Deden Riyandi (Universitas Muhammadiyah Enrekang, 2023)
The quality of Indonesian education based on UNESCO data in Global Education Monitoring (GEM) 2016, education in Indonesia ranks 10th out of 14 developing countries. This shows that the quality of school principals is also low, because school principals play a very important role in influencing the quality of education The purpose of this study is to determine the Personality Competence of school principals in Islamic Education from the perspective of Tafsir Al-Qur'an. This research is a library research, with qualitative analysis descriptive method. Researchers describe the Principal's Personality Competence in Islamic Education, then analyze it in detail and in depth with the perspective of Tafsir Al-Qur'an. That is the book Tanwir Miqbas Min Tafsir Ibn Abbas, Tafsir Jalalain, Tafsir al Qur'an al Azim, Tafsir Al Qurtubi, Tafsir Alkassaf. The results of the research on the Competence of the Principal in the Perspective of the Qur'an are as follows: Personality competence in Islam: (1) The traits of a believer: khusyu´ and keep his prayer; abstain from (actions and words) that are useless; pay zakat; and those who keep their genitals; people who keep their trusts and promises. (2) Principal Personality: Able to be a role model; Able to lead; Leading in activities towards the best people; Establishing school policies/regulations in accordance with Islamic teachings; Leading in order to exalt the religion of Allah; Leading in Amar makruf nahi munkar; Able to establish regulations for obedience; Responsible; Resolving problems in accordance with Islamic teachings; Discipline